Negative pole piece, preparation method of negative pole piece, battery monomer, battery and power utilization device
Patent Information
- Application Number
- CN202380051346.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2025-02-18
AI Technical Summary
While increasing the energy density of existing batteries, the increase in thickness of the negative electrode leads to an intensified expansion effect, affecting ion dynamics, resulting in poor rate performance.
The design of the negative electrode plate is adopted, in which the film layer includes two parts: one part is composed of a first active material with a high compaction density and the other part is composed of a second active material with a coating layer, and the powder compaction density of the first active material is greater than The second active material improves the energy density and cycle performance of the battery through synergy.
It achieves high energy density and good charge-discharge performance and cycle performance, improves the ion dynamics of the battery and extends the service life.
Smart Images

Figure CN119487640A_ABST
Abstract
Description
Negative electrode sheet and preparation method thereof, battery cell, battery and electrical device Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a negative electrode sheet, a method for preparing a negative electrode sheet, a battery cell, a battery, and an electrical device. Background Art
[0002] In recent years, batteries have been widely used in energy storage systems such as hydropower, thermal power, wind power, and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the widespread application of batteries, higher requirements have been placed on their energy density and rate performance.
[0003] Increasing the active material loading on the negative electrode sheet is one way to improve battery energy density. However, as the active material loading increases, the thickness of the negative electrode sheet increases. This exacerbates the expansion effect of the negative electrode active material layer during battery cycling, making it more prone to collapse and seriously affecting ion dynamics. Therefore, how to achieve both high energy density and good rate performance in batteries is a pressing technical challenge.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned technical problems, and its purpose is to provide a negative electrode plate, a method for preparing a negative electrode plate, a battery cell, a battery and an electrical device. The negative electrode plate is used in a battery to enable the battery to have high energy density and good cycle performance.
[0006] In a first aspect, the present application provides a negative electrode plate, comprising: a current collector and a film layer disposed on the current collector; the film layer comprises a first portion and a second portion disposed along a thickness direction of the film layer, the first portion being disposed on the current collector, and the second portion being disposed on the first portion; the first portion comprising a first active material, the second portion comprising a second active material, the first active material comprising a first carbon-based material, the second active material comprising a second carbon-based material having a coating layer, and the powder compaction density of the first active material being greater than the powder compaction density of the second active material.
[0007] In the embodiments of the present application, on the one hand, a first active material is arranged in the first part, and the first active material has a larger compaction density than the second active material, providing a higher energy density for the battery; on the other hand, a second active material is arranged in the second part, and the second active material includes a second carbon-based material with a coating layer, so that the second active material has better ion dynamics, which helps to improve battery polarization. Therefore, the first active material arranged in the first part and the second active material arranged in the second part work synergistically, so that the battery has high energy density while also having good charge and discharge performance and cycle performance.
[0008] In some embodiments, the powder compaction density ρ2 of the second active material under a pressure of 50,000 N satisfies: 1.50 g / cc≤ρ2≤2.00 g / cc; optionally, 1.55 g / cc≤ρ2≤1.95 g / cc.
[0009] In some embodiments, the powder compaction density of the second carbon-based material under a pressure of 50,000 N is 2-1 Satisfies: 1.60g / cc≤ρ 2-1 ≤1.95g / cc, optionally, 1.65g / cc≤ρ 2-1 ≤1.80g / cc.
[0010] In some embodiments, the second carbon-based material comprises primary particles.
[0011] In an embodiment of the present application, primary particles are introduced into the second carbon-based material. On the one hand, the second carbon-based material having the morphology of primary particles is simple to prepare, easy to obtain, has a high degree of graphitization, a high gram capacity, and can provide a higher energy density for the battery. On the other hand, the second active material includes a second carbon-based material having a coating layer, in other words, includes primary particles having a coating layer. Compared with primary particles, the primary particles with a coating layer have more ion active sites on their surface, which helps to improve ion dynamics, thereby helping to improve the charge and discharge performance of the battery.
[0012] In some embodiments, the coating layer comprises amorphous carbon.
[0013] In the embodiments of the present application, the coating layer contains amorphous carbon, which helps to improve the conductivity of the second carbon-based material and increase the number of ion active sites on the surface of the second carbon-based material, thereby further improving the ion dynamics of the second active material.
[0014] In some embodiments, the second carbon-based material satisfies at least one of the following (1)-(3): (1) the specific surface area of the second carbon-based material is SSA2, 1.0m 2 / g≤SSA2≤3.0m 2 / g; optionally, 1.3m2 / g≤SSA2≤2.0m 2 / g; (2) the volume particle size distribution of the second carbon-based material is D V 502, 6.0μm≤D V 502≤18.0μm; optionally, 8.0μm≤D V 502≤15.0μm; (3) the mass specific capacity of the second carbon-based material is C m2 , 345mAh / g≤C m2 ≤360mAh / g; optionally, 348mAh / g≤C m2 ≤358mAh / g.
[0015] In some embodiments, the powder compaction density ρ1 of the first active material under a pressure of 50,000 N satisfies: 1.70 g / cc≤ρ1≤2.05 g / cc; optionally, 1.80 g / cc≤ρ1≤2.05 g / cc.
[0016] In an embodiment of the present application, when a first active material is provided in the first part of the membrane layer and a second active material is provided in the second part of the membrane layer, by controlling the powder compaction density of the first active material within an appropriate range, the inner side of the membrane layer close to the current collector has a higher powder compaction density, thereby providing a high energy density for the battery.
[0017] In some embodiments, the powder compaction density of the first carbon-based material under a pressure of 50,000 N is 1-1 Satisfies: 1.80g / cc≤ρ 1-1 ≤2.05g / cc; optionally, 1.90g / cc≤ρ 1-1 ≤2.00g / cc.
[0018] The embodiments of the present application help to increase the powder compaction density of the first active material by controlling the powder compaction density of the first carbon-based material within a suitable range, thereby increasing the powder compaction density inside the membrane layer and providing high energy density for the battery.
[0019] In some embodiments, the first carbon-based material includes artificial graphite that has been subjected to a slight oxidation treatment.
[0020] In an embodiment of the present application, the first carbon-based material includes artificial graphite that has been subjected to micro-oxidation treatment. Compared with ordinary artificial graphite, the artificial graphite that has been subjected to micro-oxidation treatment has a larger specific surface area, greater adhesion between particles, and a high powder compaction density.
[0021] In some embodiments, the first carbon-based material includes secondary particles.
[0022] In the embodiments of the present application, the introduction of secondary particles into the first carbon-based material helps improve the ion dynamics of the first carbon-based material, thereby improving the ion dynamics of the first active material disposed in the first portion. This further enhances the ion conductivity of the negative electrode plate, helping to improve the battery's charge and discharge performance. Furthermore, the strong bonding between the secondary particles creates a strong cohesive force within the negative electrode plate, which helps to mitigate the expansion effect of the negative electrode plate during battery cycling, thereby improving the battery's cycling performance and service life.
[0023] In some embodiments, in the first carbon-based material, the number of secondary particles accounts for n and satisfies: 70%≤n≤90%.
[0024] In some embodiments, the first carbon-based material satisfies at least one of the following (4)-(6): (4) The specific surface area of the first carbon-based material is SSA1, 1.6 m 2 / g≤SSA1≤3.5m 2 / g; optionally, 1.8m 2 / g≤SSA1≤2.8m 2 / g; (5) the volume particle size distribution of the first carbon-based material is D V 501, 10.0μm≤D V 501≤30.0μm; optionally, 13.0μm≤D V 501≤25.0μm; (6) the mass specific capacity of the first carbon-based material is C m1 , 350mAh / g≤C m1 ≤365mAh / g; optionally, 355mAh / g≤C m1 ≤362mAh / g.
[0025] In some embodiments, the first active material further comprises natural graphite.
[0026] In the embodiments of the present application, the introduction of natural graphite into the first active material helps to increase the gram capacity of the first active material, and further helps to improve the energy density of the battery.
[0027] In some embodiments, the ratio of the mass m2 of the natural graphite to the mass m1 of the first active material satisfies: 0%<m2 / m1≤50%.
[0028] In some embodiments, a ratio of the thickness h1 of the first portion to the thickness h of the film layer satisfies: 40%≤h1 / h≤60%.
[0029] In some embodiments, a ratio of a thickness h2 of the second portion to a thickness h of the film layer satisfies: 40%≤h2 / h≤60%.
[0030] In the embodiments of the present application, by controlling the proportion of the thickness h1 of the first part and / or the thickness h2 of the second part in the thickness h of the film layer, the energy density of the negative electrode plate can be flexibly adjusted according to the needs of different batteries to adapt to more different models of batteries.
[0031] In a second aspect, a method for preparing a negative electrode sheet is provided, the method comprising: providing a current collector; preparing a first portion of a film layer on the current collector; wherein the first portion comprises a first active material, and the first active material comprises a first carbon-based material; preparing a second portion of the film layer on the first portion of the film layer, wherein the second portion comprises a second active material, and the second active material comprises a second carbon-based material having a coating layer, and the powder compaction density of the first active material is greater than the powder compaction density of the second active material.
[0032] In the examples of this application, the membrane layer is prepared to include a first portion comprising a first active material and a second portion comprising a second active material. The first carbon-based material in the first active material has a high compaction density, which can provide a high energy density for the battery. The second carbon-based material in the second active material has a coating layer, which enables the negative electrode plate to have good ion dynamics. The negative electrode plate prepared by this method not only realizes a high energy density battery, but also provides good charge and discharge performance and cycling performance.
[0033] In a third aspect, a battery cell is provided, wherein the battery cell comprises the negative electrode sheet described in any embodiment of the first aspect, or the negative electrode sheet prepared according to the method described in any embodiment of the second aspect.
[0034] In a fourth aspect, a battery is provided, comprising the battery cell described in any embodiment of the third aspect.
[0035] In a fifth aspect, an electrical device is provided, which includes the battery cell described in any embodiment of the third aspect and / or the battery described in any embodiment of the fourth aspect.
[0036] Therefore, the negative electrode plate provided in the embodiment of the present application can realize a high energy density battery by designing the film layer and the materials of different parts of the film layer, while also making the battery have good charge and discharge performance, cycle performance and service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. Those skilled in the art can also derive other drawings based on the drawings without inventive effort. In the drawings, the drawings are not drawn to scale.
[0038] FIG1 is a schematic structural diagram of a negative electrode plate of the present application.
[0039] FIG2 is a schematic flow chart of a method for preparing a negative electrode sheet according to the present application.
[0040] FIG3 is a schematic diagram of a battery cell of the present application.
[0041] FIG4 is a schematic diagram of a battery module of the present application.
[0042] FIG5 is a schematic diagram of a battery according to the present application.
[0043] FIG6 is another schematic diagram of a battery according to the present application. DETAILED DESCRIPTION
[0044] Below, with appropriate reference to the accompanying drawings, the embodiments of the negative electrode sheet, the method for preparing the negative electrode sheet, the battery cell, the battery, and the electrical device of the present application are described in detail. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0045] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0046] In the description of this application, it should be noted that, unless otherwise specified, "multiple" means more than two; the terms "upper", "lower", "left", "right", "inside", "outside", etc., indicating directions or positional relationships, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on this application. In addition, the terms "first", "second", "third", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance. "Vertical" is not strictly perpendicular, but is within the allowable error range. "Parallel" is not strictly parallel, but is within the allowable error range.
[0047] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0048] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0049] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0050] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0051] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0052] Unless otherwise specified, the following terms have the following meanings. Any undefined terms have their generally accepted meanings in the art.
[0053] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery's charge and discharge process, active ions are embedded in and released from the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator is positioned between the positive and negative electrodes, primarily to prevent a short circuit between the positive and negative electrodes while allowing ions to pass through. In some embodiments, the battery described herein is also referred to as a secondary battery.
[0054] This application uses lithium-ion batteries as an example. Lithium-ion batteries are a typical type of secondary battery. Because they rely on the chemical reaction of lithium ions intercalating and disintercalating between the positive and negative electrodes to charge and discharge, lithium-ion batteries are also called rocking-chair batteries. During charging, lithium ions are released from the positive electrode, moved to the negative electrode, and then intercalated. During discharge, lithium ions are released from the negative electrode, moved to the positive electrode, and then intercalated.
[0055] It should be understood that the "lithium insertion" and "intercalation" processes described in this application refer to the process in which lithium ions are embedded in the positive electrode material and the negative electrode material due to electrochemical reactions, and the "de-lithiumization", "de-lithiumization" and "de-intercalation" processes described in this application refer to the process in which lithium ions are removed from the positive electrode material and the negative electrode material due to electrochemical reactions.
[0056] First, some technical terms involved in the embodiments of this application are introduced.
[0057] "Carbon-based materials" refer to materials with carbon as the matrix, including carbon-based composites, fiber-reinforced composites, graphite and graphene materials, etc.
[0058] "Micro-oxidation treatment" refers to the process of placing the material in an oxidizing atmosphere at a temperature of 600°C-900°C to carry out a micro-oxidation reaction.
[0059] "Primary particles" refer to carbon-based particles obtained by direct crushing, shaping, graphitization, etc. of raw materials, also known as carbon-based single particles.
[0060] "Secondary particles" refer to particles with a carbon matrix, which are formed from primary particles through agglomeration, granulation or other means, and then obtained through steps such as graphitization.
[0061] With the increasing application of batteries, higher requirements are placed on the energy density of batteries. Increasing the powder compaction density of the positive and negative electrode sheets allows the positive and negative electrode sheets to carry more positive and negative active materials per unit area or volume, which can effectively improve the energy density of the battery. Taking the negative electrode sheet as an example, the thicker the film layer of the negative electrode sheet and the greater the compaction density, the higher the energy density that the negative electrode sheet can contribute. However, the current collector can only withstand a limited amount of compression, and a thicker film layer will cause the expansion effect of the negative electrode sheet to intensify during the battery cycle. The film layer is more likely to collapse, which is not conducive to the release and embedding of active ions in the negative electrode active material, thereby seriously affecting the ion dynamics of the battery and resulting in poor rate performance.
[0062] In view of this, an embodiment of the present application provides a negative electrode plate, the film layer of the negative electrode plate includes a first part arranged on the negative electrode collector and a second part arranged on the first part, the first part includes a first active material, the second part includes a second active material, and the first active material includes a first carbon-based material with a larger compaction density, and the second active material includes a second carbon-based material with a coating layer. The synergistic effect of the first carbon-based material and the second carbon-based material enables the negative electrode plate to provide a high energy density for the battery while also helping to improve the charge and discharge performance and cycle performance of the battery.
[0063] Next, the negative electrode sheet, positive electrode sheet, separator and other parts of the battery are introduced in detail.
[0064] [Negative electrode]
[0065] The negative electrode sheet generally includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material. It should be understood that the negative electrode film layer is a film layer disposed on the negative electrode current collector.
[0066] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0067] Alternatively, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base layer (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0068] Alternatively, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0069] Optionally, the negative electrode film layer further includes a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0070] Optionally, in one embodiment, the negative electrode film layer further includes a conductive agent, which can be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0071] Optionally, the negative electrode film layer further includes other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)).
[0072] FIG1 is a schematic structural diagram of a negative electrode plate provided in an embodiment of the present application.
[0073] As shown in FIG1 , the negative electrode plate 1 includes a negative electrode current collector 11 and a film layer 12 disposed on the negative electrode current collector 11 .
[0074] The film layer 12 includes a first portion 12a and a second portion 12b. The first portion 12a is disposed on the negative electrode current collector 11, and the second portion 12b is disposed on the first portion 12a.
[0075] The first part 12a includes a first active material including a first carbon-based material; the second part 12b includes a second active material including a second carbon-based material having a coating layer, and the powder compaction density of the first active material is greater than the powder compaction density of the second active material.
[0076] Specifically, the film layer 12 is the above-mentioned negative electrode film layer. In the negative electrode plate 1, the first portion 12a of the film layer 12 is provided with a first active material, and the second portion 12b of the film layer 12 is provided with a second active material. The powder compaction density of the first active material is greater than that of the second active material. Therefore, the inner film layer 12 of the negative electrode plate 1 away from the electrolyte has a higher compaction density, which can provide a higher energy density for the battery. The coating layer on the surface of the second carbon-based material can provide a large number of active sites for the electrochemical reaction of the battery, which helps to improve the ion dynamics of the outer film layer 12 of the negative electrode plate 1 close to the electrolyte, thereby providing the battery with good charge and discharge capacity and cycle performance.
[0077] Optionally, the powder compaction density ρ2 of the second active material under a pressure of 50,000 N satisfies: 1.50 g / cc≤ρ2≤2.00 g / cc; optionally, 1.55 g / cc≤ρ2≤1.95 g / cc.
[0078] Specifically, ρ2 can be 1.50g / cc, 1.55g / cc, 1.60g / cc, 1.65g / cc, 1.70g / cc, 1.75g / cc, 1.80g / cc, 1.85g / cc, 1.90g / cc, 1.95g / cc, 2.00g / cc, or its value is within the range obtained by combining any two of the above values.
[0079] Optionally, the powder compaction density of the second carbon-based material under a pressure of 50000N is 2-1 Satisfies: 1.60g / cc≤ρ 2-1 ≤1.95g / cc; optionally, 1.65g / cc≤ρ 2-1 ≤1.80g / cc.
[0080] Optionally, the second carbon-based material comprises primary particles.
[0081] Specifically, primary particles have the advantages of simple preparation method, easy acquisition, high degree of graphitization and high specific capacity.
[0082] In this embodiment, by introducing primary particles into the second carbon-based material, the outer film layer 12 of the negative electrode plate 1 also has a high energy density. Furthermore, the second active material comprises the second carbon-based material with a coating layer, in other words, comprises primary particles with a coating layer. The coating layer significantly increases the number of electrochemically active sites on the surface of the primary particles, helping to improve the ion dynamics of the outer film layer 12 of the negative electrode plate 1, i.e., the surface of the negative electrode plate 1, thereby further enhancing the battery's charge-discharge and cycling performance.
[0083] It should be understood that primary particles are a morphological property of a material. The second carbon-based material includes primary particles, and the second carbon-based material may be entirely primary particles, or a portion of the second carbon-based material may be primary particles, while the remaining second carbon-based material does not have the morphology of primary particles.
[0084] Optionally, the coating layer comprises amorphous carbon.
[0085] Specifically, amorphous carbon has the advantages of high electrical conductivity and numerous electrochemically active sites.
[0086] In this embodiment, by introducing amorphous carbon into the coating layer, the second carbon-based material has good conductivity and increases the number of electrochemically active sites on the surface of the second carbon-based material. This improves the ion dynamics of the outer film layer 12 of the negative electrode plate 1, thereby helping to improve the charge-discharge performance and cycling performance of the battery.
[0087] Optionally, the second carbon-based material satisfies at least one of the following (1)-(3):
[0088] (1) The specific surface area of the second carbon-based material is SSA2, 1.0m 2 / g≤SSA2≤3.0m 2 / g; optionally, 1.3m 2 / g≤SSA2≤2.0m 2 / g.
[0089] (2) The volume particle size distribution of the second carbon-based material is D V 502, 6.0μm≤D V 502≤18.0μm; optionally, 8.0μm≤D V 502≤15.0μm.
[0090] (3) The mass specific capacity of the second carbon-based material is C m2 , 345mAh / g≤C m2 ≤360mAh / g; optionally, 348mAh / g≤C m2 ≤358mAh / g.
[0091] Specifically, SSA2 can be 1.0m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g, 2.2m 2 / g, 2.4m 2 / g, 2.6m 2 / g, 2.8m 2 / g, 3.0m 2 / g, or its value is within the range obtained by combining any two of the above values.
[0092] D V 502 can be 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, or a value within the range obtained by combining any two of the above values.
[0093] C m2 It can be 345mAh / g, 346mAh / g, 347mAh / g, 348mAh / g, 349mAh / g, 350mAh / g, 352mAh / g, 354mAh / g, 356mAh / g, 358mAh / g, 360mAh / g, or its numerical range is within the range obtained by combining any two of the above numerical values.
[0094] Optionally, the powder compaction density ρ1 of the first active material under a pressure of 50,000 N satisfies: 1.70 g / cc≤ρ1≤2.05 g / cc; optionally, 1.80 g / cc≤ρ1≤2.05 g / cc.
[0095] Specifically, ρ1 can be 1.70g / cc, 1.72g / cc, 1.74g / cc, 1.76g / cc, 1.80g / cc, 1.82g / cc, 1.84g / cc, 1.86g / cc, 1.88g / cc, 2.00g / cc, 2.02g / cc, 2.04g / cc, 2.05g / cc, or its value is within the range obtained by combining any two of the above values.
[0096] In this embodiment, by controlling the powder compaction density ρ1 of the first active material within an appropriate range, on the one hand, the first part 12a of the film layer 12 has a higher powder compaction density, thereby increasing the contribution of the first part 12a to the energy density of the negative electrode plate 1; on the other hand, the powder compaction density of the first part 12a is controlled not to exceed the threshold value, thereby reducing the possibility of damaging the negative electrode current collector.
[0097] Optionally, the powder compaction density of the first carbon-based material under a pressure of 50,000 N is 1-1 Satisfies: 1.80g / cc≤ρ 1-1 ≤2.05g / cc; optionally, 1.90g / cc≤ρ 1-1 ≤2.00g / cc.
[0098] Specifically, ρ 1-1 It can be 1.80 g / cc, 1.85 g / cc, 1.90 g / cc, 1.95 g / cc, 2.00 g / cc, 2.05 g / cc, or a value within the range obtained by combining any two of the above values.
[0099] In this embodiment, by controlling the powder compaction density ρ of the first carbon-based material 1-1 Within a suitable range, it helps to increase the powder compaction density ρ1 of the first active material, thereby helping to increase the powder compaction density of the first portion 12a of the film layer 12, providing a high energy density for the battery while reducing the possibility of damaging the negative electrode current collector.
[0100] Optionally, the first carbon-based material includes artificial graphite that has been subjected to a slight oxidation treatment.
[0101] Specifically, compared to conventional artificial graphite, artificial graphite that has undergone a micro-oxidation treatment has the advantages of larger particle size, higher degree of graphitization, higher specific capacity, and higher powder compaction density. As the first carbon-based material, or part of the first carbon-based material, it can contribute high energy density to the negative electrode plate 1. Furthermore, the micro-oxidation treatment enhances the adhesion between artificial graphite particles, resulting in stronger cohesion in the inner film layer 12 of the negative electrode plate 1 and less expansion during battery cycling, thereby helping to improve the battery's cycling performance and service life.
[0102] Optionally, the first carbon-based material comprises secondary particles.
[0103] Specifically, due to the formation and characteristics of the secondary particles themselves, in the electrochemical reaction, the secondary particles can expose more active sites, thereby helping to improve the ion dynamics of the battery.
[0104] In this embodiment, by introducing secondary particles into the first carbon-based material, the active sites of the first carbon-based material in the electrochemical reaction can be increased, which helps to increase the active sites of the first active material. As a result, the inner film layer 12 of the negative electrode plate 1 away from the electrolyte also has good ion dynamics, which helps to further improve the charge and discharge performance of the battery.
[0105] It should be understood that secondary particles are a morphological property of the material. The first carbon-based material includes secondary particles, and the first carbon-based material may be entirely or partially secondary particles.
[0106] In one example, the first carbon-based material is artificial graphite after micro-oxidation treatment. The artificial graphite after micro-oxidation treatment may be all secondary particles, or only a portion of the artificial graphite after micro-oxidation treatment may be secondary particles, and the remaining artificial graphite after micro-oxidation treatment does not have the morphology of secondary particles.
[0107] In another example, the first carbon-based material includes artificial graphite after micro-oxidation treatment and artificial graphite. The artificial graphite after micro-oxidation treatment may be secondary particles, and the artificial graphite does not have the morphology of secondary particles; the artificial graphite may be secondary particles, and the artificial graphite after micro-oxidation treatment does not have the morphology of secondary particles; the artificial graphite after micro-oxidation treatment and the artificial graphite may both be secondary particles; and part of the artificial graphite after micro-oxidation treatment and part of the artificial graphite are secondary particles, and the remaining artificial graphite after micro-oxidation treatment and the remaining artificial graphite do not have the morphology of secondary particles.
[0108] Optionally, in the first carbon-based material, the proportion n of the secondary particles satisfies: 70%≤n≤90%.
[0109] Specifically, n may be 70%, 75%, 80%, 85%, 90%, or any value within the range obtained by combining any two of the above values.
[0110] Optionally, the first carbon-based material satisfies at least one of the following (4)-(6):
[0111] (4) The specific surface area of the first carbon-based material is SSA1, 1.6 m 2 / g≤SSA1≤3.5m 2 / g; optionally, 1.8m 2 / g≤SSA1≤2.8m 2 / g.
[0112] (5) The volume particle size distribution of the first carbon-based material is D V 501, 10.0μm≤D V 501≤30.0μm; optionally, 13.0μm≤DV 501≤25.0μm.
[0113] (6) The mass specific capacity of the first carbon-based material is C m1 , 350mAh / g≤C m1 ≤365mAh / g; optionally, 355mAh / g≤C m1 ≤362mAh / g.
[0114] Specifically, SSA1 can be 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g, 2.1m 2 / g, 2.2m 2 / g, 2.3m 2 / g, 2.4m 2 / g, 2.5m 2 / g, 2.6m 2 / g, 2.7m 2 / g, 2.8m 2 / g, 2.9m 2 / g, 3.0m 2 / g, 3.1m 2 / g, 3.2m 2 / g, 3.3m 2 / g, 3.4m 2 / g, 3.5m 2 / g, or its value is within the range obtained by combining any two of the above values.
[0115] D V 501 can be 10μm, 12μm, 13μm, 14μm, 16μm, 18μm, 20μm, 22μm, 24μm, 25μm, 26μm, 28μm, 30μm, or its value is within the range obtained by combining any two of the above values.
[0116] C m1 It can be 350mAh / g, 352mAh / g, 354mAh / g, 355mAh / g, 356mAh / g, 358mAh / g, 360mAh / g, 362mAh / g, 364mAh / g, 365mAh / g, or its numerical range is within the range obtained by combining any two of the above numerical values.
[0117] Optionally, the first active material further includes natural graphite.
[0118] Natural graphite has a higher specific capacity than artificial graphite. In this embodiment, the introduction of natural graphite into the first active material helps increase the specific capacity of the first active material. This further increases the energy density of the inner film layer 12 of the negative electrode plate 1, thereby further improving the energy density of the battery.
[0119] Optionally, the ratio of the mass m2 of the natural graphite to the mass m1 of the first active material satisfies: 0%<m2 / m1≤50%.
[0120] Specifically, m2 / m1 can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or its numerical range is within the range obtained by combining any two of the above numerical values.
[0121] It should be understood that in the case where the first active material does not include natural graphite, m2 / m1 may be 0.
[0122] Optionally, as shown in FIG1 , the ratio of the thickness h1 of the first portion 12 a to the thickness h of the film layer 12 satisfies: 40%≤h1 / h≤60%.
[0123] Specifically, h1 / h can be 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, or its value is within the range obtained by combining any two of the above values.
[0124] Optionally, as shown in FIG1 , the ratio of the thickness h2 of the second portion 12 b to the thickness h of the film layer 12 satisfies: 40%≤h2 / h≤60%.
[0125] Specifically, h2 / h can be 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, or its value is within the range obtained by combining any two of the above values.
[0126] In this embodiment, by controlling the proportion of the thickness of the first part 12a and the second part 12b of the film layer 12 in the film layer 12, the energy density of the negative electrode plate 1 can be flexibly adjusted according to the needs of different batteries to adapt to more different types of batteries.
[0127] In some embodiments, the negative electrode sheet 1 can be prepared by forming the above-mentioned components for preparing the negative electrode sheet into negative electrode slurries. For example, a first active material, a conductive agent, a binder, and any other components are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a first slurry. A second active material, a conductive agent, a binder, and any other components are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a second slurry. The first and second slurries are then coated on the negative electrode current collector. After drying, cold pressing, and other processes, the negative electrode sheet 1 can be obtained.
[0128] [Positive electrode]
[0129] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0130] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0131] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0132] In some embodiments, the positive electrode active material may adopt the positive electrode active material for batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0133] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.
[0134] In some embodiments, the positive electrode film layer may further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0135] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0136] [Electrolytes]
[0137] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0138] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0139] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0140] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0141] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0142] [Isolation film]
[0143] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0144] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0145] Next, the method for preparing the negative electrode sheet according to the embodiment of the present application is introduced in detail.
[0146] FIG2 is a schematic flow chart of a method for preparing a negative electrode sheet according to an embodiment of the present application. As shown in FIG2 , method 200 includes:
[0147] S201, providing a current collector 11.
[0148] S202 , preparing a first portion 12 a of the film layer 12 on the current collector.
[0149] S203 , preparing the second portion 12 b of the film layer 12 on the first portion 12 a .
[0150] The first part 12a includes a first active material, which includes a first carbon-based material; the second part 12b includes a second active material, which includes a second carbon-based material having a coating layer; and the powder compaction density of the first active material is greater than the powder compaction density of the second active material.
[0151] In this embodiment, the film layer 12 of the negative electrode plate 1 is prepared in the form of a first part 12a and a second part 12b, wherein the first part 12a includes a first active material with a large powder compaction density, which can provide a large active material loading for the negative electrode plate 1 and a large energy density for the battery; the second part 12b includes a second carbon-based material with a coating layer, which can provide good ion dynamics for the negative electrode plate 1, thereby helping to improve the charge and discharge performance and cycle performance of the battery.
[0152] Optionally, in S202, preparing the first portion 12a of the film layer 12 on the current collector includes:
[0153] S2011, preparing a first active material.
[0154] S2012, preparing the first active material into a first slurry.
[0155] S2013 , coating the first slurry on the current collector 11 to form a first portion 12 a .
[0156] Optionally, in S2011, preparing the first active material includes:
[0157] S2011-1, preparation of artificial graphite.
[0158] S2011-2, put artificial graphite into the furnace, at 600℃-900℃, air flow rate 1m 3 / h-9m 3 / h, and a furnace tube rotation speed of 2r / min-6r / min to perform a micro-oxidation reaction to obtain a first carbon-based material; the first carbon-based material includes secondary particles.
[0159] In this embodiment, the above method can be used to prepare a first carbon-based material containing secondary particles, which not only helps to improve the energy density of the battery, but also helps to improve the expansion effect of the negative electrode during the battery cycle, thereby helping to improve the cycle performance and service life of the battery.
[0160] Optionally, in S2011-1, preparing artificial graphite includes:
[0161] S2011-1a, crushing raw materials, raw materials include coke.
[0162] S2011-1b, classifying the crushed raw materials to obtain a particle product whose volume particle size is within a preset volume particle size distribution range.
[0163] S2011-1c, shaping and removing fine powder from the granular product to obtain a first intermediate product.
[0164] S2011-1d, heat-treating the first intermediate product to obtain a second intermediate product.
[0165] S2011-1e, graphitizing the second intermediate product at 2800° C.-3200° C. to obtain artificial graphite.
[0166] Optionally, the powder compaction density ρ1 of the first active material under a pressure of 50,000 N satisfies: 1.70 g / cc≤ρ1≤2.05 g / cc; optionally, 1.80 g / cc≤ρ1≤2.05 g / cc.
[0167] Optionally, the powder compaction density ρ2 of the second active material under a pressure of 50,000 N satisfies: 1.50 g / cc≤ρ2≤2.00 g / cc; optionally, 1.55 g / cc≤ρ2≤1.95 g / cc.
[0168] Optionally, the powder compaction density ρ1 of the first carbon-based material under a pressure of 50,000 N satisfies: 1.80 g / cc ≤ ρ 1-1 ≤2.05g / cc; optionally, 1.90g / cc≤ρ 1-1 ≤2.00g / cc.
[0169] Optionally, in the first carbon-based material, the proportion n of the secondary particles satisfies: 70%≤n≤90%.
[0170] Optionally, the first carbon-based material satisfies at least one of the following (4)-(6):
[0171] (4) The specific surface area of the first carbon-based material is SSA1, 1.6m 2 / g≤SSA1≤3.5m 2 / g, optionally, 1.8m 2 / g≤SSA1≤2.8m 2 / g.
[0172] (5) The volume particle size distribution of the first carbon-based material is D V 501, 10.0μm≤D V 501≤30.0μm; optionally, 13.0μm≤D V 501≤25.0μm.
[0173] (6) The mass specific capacity of the first carbon-based material is Cm1, 350 mAh / g≤C m1 ≤365mAh / g; optionally, 355mAh / g≤C m1 ≤362mAh / g.
[0174] Optionally, in S2011, preparing the first active material includes:
[0175] S2011-3, adding natural graphite to the first carbon-based material.
[0176] Optionally, the ratio of the mass m2 of the natural graphite to the mass m1 of the first active material satisfies: 0%≤m2 / m1≤50%.
[0177] Optionally, in S203, preparing the second portion 12b of the film layer 12 on the first portion 12a includes:
[0178] S2031, preparing a second active material.
[0179] S2032, preparing the second active material into a second slurry.
[0180] S2033 , coating a second slurry on the first portion 12 a of the film layer 12 to form a second portion 12 b .
[0181] Optionally, in S2031, preparing the second active material includes:
[0182] S2031-1, prepare a second carbon-based material.
[0183] S2031-2, preparing a coating layer outside the second carbon-based material to obtain a second carbon-based material having a coating layer.
[0184] Optionally, in S2031-1, preparing the second carbon-based material includes:
[0185] S2031-1a, crushing raw materials, raw materials include coke.
[0186] S2031-1b, classifying the crushed raw materials to obtain a particle product having a volume particle size within a preset volume particle size distribution range.
[0187] S2031-1c, shaping and de-segmenting the granular product to obtain a first intermediate product.
[0188] S2031-1d, heat-treating the first intermediate product to obtain a second intermediate product.
[0189] S2031-1e, graphitizing the second intermediate product at 2800° C.-3200° C. to obtain a second carbon-based material, wherein the second carbon-based material includes primary particles.
[0190] In this embodiment, the second carbon-based material prepared by the above method includes primary particles, thereby helping to improve the charge and discharge performance and cycle performance of the battery while increasing the energy density of the battery.
[0191] Optionally, in S2031-2, preparing a coating layer outside the second carbon-based material includes:
[0192] S2031-2a, mixing asphalt with a second carbon-based material to obtain a third intermediate product.
[0193] S2031-2b, carbonizing the third intermediate product at 800° C.-1400° C. to obtain a second carbon-based material having a coating layer, wherein the coating layer includes amorphous carbon.
[0194] In this embodiment, the above method can be used to prepare a second carbon-based material having a coating layer, and the coating layer contains amorphous carbon, thereby helping to improve the ion dynamics of the negative electrode plate 1, thereby helping to improve the charge and discharge performance and cycle performance of the battery.
[0195] Optionally, the powder compaction density of the second carbon-based material under a pressure of 50000N is 2-1 Satisfies: 1.60g / cc≤ρ 2-1 ≤1.95g / cc, optionally, 1.65g / cc≤ρ 2-1 ≤1.80g / cc.
[0196] Optionally, the second carbon-based material satisfies at least one of the following (1)-(3):
[0197] (1) The specific surface area of the second carbon-based material is SSA2, 1.0m 2 / g≤SSA2≤3.0m 2 / g; optionally, 1.3m 2 / g≤SSA2≤2.0m 2 / g.
[0198] (2) The volume particle size distribution of the second carbon-based material is D V 502, 6.0μm≤D V 502≤18.0μm; optionally, 8.0μm≤D V 502≤15.0μm.
[0199] (3) The mass specific capacity of the second carbon-based material is C m2 , 345mAh / g≤Cm2 ≤360mAh / g; optionally, 348mAh / g≤C m2 ≤358mAh / g.
[0200] In some embodiments, the positive electrode sheet, the negative electrode sheet 1 and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0201] In some embodiments, the battery cell may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0202] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the battery cell may be a soft shell, such as a pouch-type soft shell. The soft shell may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0203] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square, or any other shape. For example, FIG3 shows a battery cell 300 having a square structure as an example.
[0204] Figure 4 shows an example battery module 400. Referring to Figure 4 , in the battery module 400, multiple battery cells 300 may be arranged sequentially along the length of the battery module 400. Of course, they may also be arranged in any other manner. Furthermore, the multiple battery cells 300 may be secured together using fasteners.
[0205] Optionally, in one embodiment, the battery module 400 may further include a housing having an accommodation space, and the plurality of battery cells 300 may be accommodated in the accommodation space.
[0206] Optionally, in one embodiment, the battery modules 400 may be assembled into a battery. The battery may contain one or more battery modules 400. The specific number may be selected by those skilled in the art according to the application and capacity of the battery.
[0207] Figures 5 and 6 illustrate an example battery 500. Referring to Figures 5 and 6, the battery 500 may include a battery box and multiple battery modules 400 disposed within the box. The battery box includes an upper case 501 and a lower case 502. The upper case 501 can be placed over the lower case 502 to form an enclosed space for accommodating the battery modules 400. The multiple battery modules 400 can be arranged in any manner within the battery box.
[0208] It should be understood that in other embodiments, the battery 500 is also referred to as a battery pack. The battery cells 300 may first be assembled into the battery module 400, and the battery 500 may be assembled from the battery module 400. Alternatively, the battery 500 may be assembled directly from the battery cells 300, omitting the intermediate battery module 400.
[0209] In addition, the present application also provides an electrical device, which includes at least one of the battery cell 300, battery module 400, or battery 500 provided in the present application. The battery cell 300, battery module 400, or battery 500 can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0210] As an electric device, a battery cell 300 , a battery module 400 , or a battery 500 may be selected according to its usage requirements.
[0211] As an example of an electric device, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the electric device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module can be used.
[0212] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0213] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0214] [Examples 1-26 and Comparative Examples 1-3]
[0215] Example 1
[0216] (1) Preparation of positive electrode sheet
[0217] The positive electrode active material, lithium iron phosphate, the conductive agent, acetylene black, and the binder, polyvinylidene fluoride (PVDF), are dissolved in the solvent N-methylpyrrolidone (NMP) and thoroughly stirred to form a positive electrode slurry. The slurry is then evenly coated onto the positive electrode current collector aluminum foil, dried, cold pressed, and slit to form the positive electrode sheets. The ratio of the mass of the positive electrode active material to the sum of the mass of the positive electrode active material, conductive agent, and binder is 95%-98%; alternatively, the ratio is 96%-97%.
[0218] (2) Preparation of negative electrode sheet
[0219] The first active material, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water and mixed evenly to obtain a first slurry. The second active material, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are dissolved in deionized water and mixed evenly to obtain a second slurry. The first slurry is then evenly coated on the negative electrode current collector copper foil and dried to form the first portion 12a of the film layer 12. The second slurry is then evenly coated on the first portion 12a and dried to form the second portion 12b of the film layer 12. The negative electrode sheet is then cold pressed and slit. The first active material is artificial graphite that has undergone a micro-oxidation treatment; the second active material is primary particles with a coating layer.
[0220] In Example 1, the artificial graphite after micro-oxidation treatment is the first carbon-based material and also the first active material. The powder compaction density of the first carbon-based material is 1-1 is 1.95 g / cc, the powder compaction density of the first active material ρ1 is 1-1 The volume particle size distribution of the first carbon-based material is equal to 1.95 g / cc. V 501 is 18μm, the mass specific capacity C of the first carbon-based material m1 The ratio of secondary particles in the first carbon-based material to m2 / m1 is 80%. The primary particles are the second carbon-based material, and the primary particles with the coating layer are the second active material. The powder compaction density ρ2 of the second active material is 1.7g / cc, and the powder compaction density ρ 2-1 The volume particle size distribution D of the second carbon-based material is 1.7 g / cc. V 502 is 10 μm, the mass specific capacity C of the second carbon-based material m2 It is 350mAh / g.
[0221] It should be understood that the above-mentioned powder compaction density is the powder compaction density under a pressure of 50,000 N. The materials with the above-mentioned volume particle size distribution can be tested by gas adsorption method to obtain the corresponding specific surface area, which will not be repeated here.
[0222] (3) Assembly of battery cells
[0223] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order so that the separator is located between the positive electrode sheet and the negative electrode sheet and can isolate the positive electrode sheet from the negative electrode sheet; the stacked components are then wound to obtain an electrode assembly; the electrode assembly is placed in a shell, dried, and then injected with a LiPF6 electrolyte with a mass fraction of 11%; after processes such as formation and standing, a battery cell 300 is obtained.
[0224] Example 2
[0225] Compared with Example 1, the first active material of the negative electrode plate in Example 2 further includes natural graphite, wherein the mass ratio of natural graphite to the first active material m2 / m1 is 50%, the powder compaction density ρ1 of the first active material is 1.98 g / cc, and the powder compaction density ρ of the first carbon-based material (slightly oxidized natural graphite) is 1. 1-1 It is 1.95g / cc.
[0226] Example 3
[0227] Compared with Example 1, Example 3 only changes the powder compaction density of the first active material in the negative electrode sheet, that is, ρ1 in Example 3 is 1.8 g / cc.
[0228] Example 4
[0229] Compared with Example 1, Example 4 only changes the powder compaction density of the first active material in the negative electrode sheet, that is, ρ1 in Example 4 is 2.05 g / cc.
[0230] Example 5
[0231] Compared with Example 1, Example 5 only changes the volume particle size distribution of the first carbon-based material in the negative electrode sheet, that is, D V 501 is 13μm.
[0232] Example 6
[0233] Compared with Example 1, Example 6 only changes the volume particle size distribution of the first carbon-based material in the negative electrode sheet, that is, D V 501 is 25μm.
[0234] Example 7
[0235] Compared with Example 1, the volume particle size distribution D of the first carbon-based material in the negative electrode sheet of Example 7 is V 501 is 8μm.
[0236] Example 8
[0237] Compared with Example 1, the volume particle size distribution D of the first carbon-based material in the negative electrode sheet of Example 8 is V 501 is 27μm.
[0238] Example 9
[0239] Compared with Example 1, Example 9 only changes the gram capacity of the first carbon-based material in the negative electrode plate, that is, Cm1 is 355 mAh / g.
[0240] Example 10
[0241] Compared with Example 1, Example 10 only changes the gram capacity of the first carbon-based material in the negative electrode plate, that is, Cm1 is 362 mAh / g.
[0242] Example 11
[0243] Compared with Example 1, the gram capacity Cm1 of the first carbon-based material in the negative electrode sheet of Example 11 is 345 mAh / g.
[0244] Example 12
[0245] Compared with Example 1, the gram capacity Cm1 of the first carbon-based material in the negative electrode sheet of Example 12 is 365 mAh / g.
[0246] Example 13
[0247] Compared with Example 1, Example 13 only changed the number ratio of the secondary particles to the first carbon-based material in the first carbon-based material, that is, m2 / m1 was 70%.
[0248] Example 14
[0249] Compared with Example 1, Example 14 only changed the number ratio of the secondary particles to the first carbon-based material in the first carbon-based material, that is, m2 / m1 was 90%.
[0250] Example 15
[0251] Compared with Example 1, in the negative electrode sheet of Example 15, the number ratio m2 / m1 of the secondary particles in the first carbon-based material is 96%.
[0252] Example 16
[0253] Compared with Example 1, the second active material of the negative electrode plate in Example 16 includes primary particles with a coating layer and secondary particles with a coating layer. In Example 16, the primary particles with a coating layer are the second carbon-based material, and the powder compaction density ρ 2-1 The powder compaction density ρ2 of the second active material is 1.70 g / cc, and the powder compaction density ρ2 of the second active material is 1.71 g / cc.
[0254] Example 17
[0255] Compared with Example 1, Example 17 only changes the powder compaction density of the second active material in the negative electrode sheet, that is, ρ2 is 1.65 g / cc.
[0256] Example 18
[0257] Compared with Example 1, Example 18 only changed the powder compaction density of the second active material in the negative electrode sheet, that is, ρ2 was 1.8 g / cc.
[0258] Example 19
[0259] Compared with Example 1, the powder compaction density ρ2 of the second active material in the negative electrode sheet of Example 19 is 1.55 g / cc.
[0260] Example 20
[0261] Compared with Example 1, Example 20 only changes the volume particle size distribution of the second carbon-based material in the negative electrode sheet, that is, D V 502 is 8μm.
[0262] Example 21
[0263] Compared with Example 1, Example 21 only changes the volume particle size distribution of the second carbon-based material in the negative electrode sheet, that is, D V 502 is 15μm.
[0264] Example 22
[0265] Compared with Example 1, the volume particle size distribution D of the second carbon-based material in the negative electrode sheet of Example 22 is V 502 are 5μm respectively.
[0266] Example 23
[0267] Compared with Example 1, Example 23 only changes the gram capacity of the second carbon-based material in the negative electrode plate, that is, Cm2 is 348 mAh / g.
[0268] Example 24
[0269] Compared with Example 1, Example 24 only changes the gram capacity of the second carbon-based material in the negative electrode plate, that is, Cm2 is 358 mAh / g.
[0270] Example 25
[0271] Compared with Example 1, the gram capacity Cm2 of the second carbon-based material in the negative electrode sheet of Example 25 is 343 mAh / g.
[0272] Example 26
[0273] Compared with Example 1, the gram capacity Cm2 of the second carbon-based material in the negative electrode sheet of Example 25 is 362 mAh / g.
[0274] Comparative Example 1
[0275] Compared with Example 1, the second active material in the negative electrode sheet of Comparative Example 1 is a primary particle without a coating layer.
[0276] Comparative Example 2
[0277] Compared with Example 1, the powder compaction density ρ1 of the first active material in the negative electrode sheet of Comparative Example 2 is 1.60 g / cc.
[0278] Comparative Example 3
[0279] Compared with Example 1, in the negative electrode sheet of Comparative Example 3, the powder compaction density ρ2 of the second active material in the negative electrode sheet of Comparative Example 3 is 2.00 g / cc.
[0280] Please refer to Table 1 for the product parameters of the embodiments and comparative examples.
[0281] In Table 1, ρ1 represents the powder compaction density of the first active material at 50,000 N, ρ 1-1 represents the powder compaction density of the first carbon-based material at 50,000 N, D V 501 represents the volume particle size distribution of the first carbon-based material, Cm1 represents the gram capacity of the first carbon-based material, n represents the number ratio of secondary particles in the first carbon-based material, m2 / m1 represents the ratio of the mass of natural graphite in the first active material to the mass of the first active material, ρ2 represents the powder compaction density of the second active material at 50000N, ρ 2-1 represents the powder compaction density of the second carbon-based material at 50000N, D V 502 represents the volume particle size distribution of the second carbon-based material, Cm1 represents the gram capacity of the second carbon-based material, "micro-oxidized AG" represents micro-oxidized artificial graphite, "NG" represents natural graphite, "primary particles" represent primary particles with a coating layer, "secondary particles" represent secondary particles with a coating layer, and "primary particles (uncoated)" represent primary particles without a coating layer.
[0282] The battery performance test results of the above Examples 1-26 and Comparative Examples 1-3 are detailed in Table 2 and Table 3.
[0283] Table 2 Charging time performance test results of different embodiments and comparative examples
[0284] Table 3: Cycle number and full charge expansion rate performance test results of different embodiments
[0285] A performance comparison between Example 1 and Comparative Examples 2 and 3 shows that the charging time of the lithium-ion battery of Example 1 is much shorter than that of the lithium-ion batteries of Comparative Examples 2 and 3. In Example 1, the powder compaction density of the first active material is greater than the powder compaction density of the second active material, while in Comparative Examples 2 and 3, the powder compaction density of the first active material is less than the powder compaction density of the second active material. This indicates that by controlling the powder compaction density of the first active material to be greater than the powder compaction density of the second active material, the lithium ion kinetics of the negative electrode sheet can be effectively improved, thereby improving the charge and discharge performance of the lithium-ion battery.
[0286] A performance comparison of the various examples and Comparative Example 1 shows that the charging times of the lithium-ion batteries in Examples 1-26 are all shorter than those in Comparative Example 1. The second active material in Examples 1-26 is a primary particle with a coating layer, while the second active material in Comparative Example 1 is a primary particle without a coating layer. This demonstrates that the use of a second carbon-based material with a coating layer can impart favorable ion dynamics to the second active material, improve battery polarization, and provide excellent charge and discharge performance for the lithium-ion battery.
[0287] Compared with Example 1, the first active material of Example 2 includes natural graphite. It can be seen from the various performances of the lithium-ion batteries of Examples 1 and 2 that the addition of natural graphite does not have a significant impact on the charge and discharge performance, cycle performance, and expansion of the lithium-ion battery. Natural graphite generally has a higher specific capacity than artificial graphite. Therefore, by introducing some natural graphite into the first active material, the energy density of the lithium-ion battery can be increased without affecting the above-mentioned performances of the lithium-ion battery.
[0288] A performance comparison between Examples 3 and 4 and Comparative Example 2 shows that the lithium-ion batteries of Examples 3 and 4 also have shorter charging times than the lithium-ion battery of Comparative Example 2. The powder compaction densities of the first active materials in Examples 3 and 4 are 1.80 g / cc and 2.05 g / cc, respectively, which are within the numerical range of 1.70 g / cc to 2.05 g / cc. In contrast, the powder compaction density of the first active material in Comparative Example 2 is 1.6 g / cc, which is outside this numerical range. This demonstrates that controlling the powder compaction density of the first active material within this numerical range improves the dynamics of the lithium-ion battery and reduces charging time.
[0289] By comparing the performance of Examples 5, 6, and 8 with that of Example 7, it can be seen that, while the charging time is better than that of the comparative example, the number of cycles of Examples 5, 6, and 8 is more than that of Example 7, and the full charge expansion ratio is less than that of Example 7. The average volume particle size (D V 501) are 13 μm, 25 μm, and 27 μm, respectively, which are within the numerical range of 10 μm-30 μm, while the average volume particle size of Example 7 is 8 μm, which exceeds the above numerical range. Therefore, it is shown that by controlling the average volume particle size of the first active material within the above numerical range, it is helpful to improve the cycle performance of the lithium-ion battery and improve the problem of battery expansion, thereby helping to improve the safety performance of the battery.
[0290] Compared with Example 9 and Example 10, the gram capacity (C m1 ) are 345mAh / g and 365mAh / g respectively, which exceeds the numerical range of 350mAh / g-365mAh / g, although the four embodiments are not much different in terms of charge and discharge performance, cycle performance, and expansion. However, in actual applications, the gram capacity of the material in Example 11 is too low, which makes the energy density of the battery too low and cannot meet the needs of actual applications well. The gram capacity of Example 12 is too high, and the preparation of raw materials is extremely difficult, which is not conducive to large-scale production and application. Therefore, by controlling the gram capacity of the first carbon-based material within the above range, the charge and discharge performance, cycle performance and expansion of the lithium-ion battery can be improved, and it is also helpful to the actual mass production and application of lithium-ion batteries.
[0291] In Examples 13-15, the proportion of secondary particles in the first carbon-based material (m2 / m1) was regulated, wherein the proportion of secondary particles in Example 13 was 70%, the proportion of secondary particles in Example 14 was 90%, and the proportion of secondary particles in the first carbon-based material in Example 15 (m2 / m1) was as high as 96%, exceeding the numerical range of 70%-90%. Under the condition that the charging time of the three examples is similar, it can be seen from the comparison of the performance data of Example 13 and Example 14 that the higher the proportion of secondary particles, the more cycles of the battery and the smaller the expansion rate. Therefore, it is shown that the introduction of secondary particles into the first carbon-based material helps to improve the ion dynamics of the electrode material and helps to improve the cycle performance of the lithium-ion battery; moreover, the strong adhesion between the secondary particles helps to improve the cohesion inside the negative electrode sheet, thereby helping to improve the expansion of the battery. According to the comparison between Example 15, Example 13 and Example 14, it can be seen that the number of cycles and the expansion of Example 15 are better than those of Example 13, but the number of cycles is reduced compared with Example 14, and the full charge expansion rate is increased, indicating that the performance of the lithium-ion battery will not increase indefinitely with the increase in the proportion of secondary particles in the first carbon-based material. In addition, an excessively high proportion of secondary particles increases the difficulty of processing the material. In other words, a first carbon-based material in which the proportion of secondary particles exceeds 90% is not easy to prepare. Therefore, by controlling the proportion of secondary particles in the first carbon-based material within the above-mentioned numerical range, the lithium-ion battery can have good charge and discharge performance, cycle performance and help improve the expansion of the lithium-ion battery.
[0292] In Example 16, the second active material includes secondary particles with a coating layer. It can be seen that, similar to Example 1, by controlling the powder compaction density of the first active material to be greater than the powder compaction density of the second active material, a lithium-ion battery with improved charge and discharge performance, cycle performance, and expansion can be obtained.
[0293] Examples 17-19 manipulated the powder compaction density of the second active material. The powder compaction densities of the second active material in Examples 17 and 19 were 1.65 g / cc and 1.80 g / cc, respectively, falling within the numerical range of 1.65 g / cc to 1.95 g / cc. However, the powder compaction density of the second active material in Example 19 was 1.55 g / cc, exceeding this numerical range. A performance comparison of Example 19 with Examples 17 and 18 reveals that while the charge-discharge performance, cycling performance, and swelling of the lithium-ion battery in Example 19 were improved compared to the comparative examples, these performances were inferior to those of Examples 17 and 18. This demonstrates that controlling the powder compaction density of the second active material within the numerical range can result in a lithium-ion battery with good charge-discharge performance, cycling performance, and reduced swelling.
[0294] The average volume particle size (D V 502) was regulated, and the average volume particle size of the second carbon-based material in Example 20 and Example 21 was 8μm and 15μm, respectively, which fell within the numerical range of 6μm-18μm. The average volume particle size of the second carbon-based material in Example 22 was 5μm, which exceeded the above numerical range. Compared with the control example, the charge and discharge performance, cycle performance and expansion of the lithium-ion batteries in Examples 20-22 were improved. Although the full charge time of Example 22 is the shortest among the above three embodiments, the number of cycles of Example 22 is less than that of Example 20 and Example 21, and the average volume particle size of the second carbon-based material in Example 22 is too small, and the material is difficult to prepare. Therefore, by controlling the average volume particle size of the second carbon-based material within the above numerical range, while improving the charge and discharge performance of the lithium-ion battery, it also helps to improve the cycle performance of the lithium-ion battery.
[0295] Examples 23-26 show the gram capacity (C m2) were regulated, and the gram capacities of Examples 23-24 were 348mAh / g and 358mAh / g, respectively, which were within the numerical range of 345mAh / g-360mAh / g, while the gram capacities of Examples 25-26 were 343mAh / g and 362mAh / g, respectively, which exceeded the above numerical range. Although the four embodiments are not much different in terms of charge and discharge performance, cycle performance, and expansion. However, in actual applications, the gram capacity of the material in Example 25 is too low, which makes the energy density of the battery too low and cannot meet the needs of actual applications well. The gram capacity of Example 26 is too high, the raw materials are expensive and difficult to obtain, and it is not conducive to large-scale production and application. Therefore, by controlling the gram capacity of the second carbon-based material within the above range, the charge and discharge performance, cycle performance and expansion of the lithium-ion battery can be improved, and it is also helpful to the actual mass production and application of lithium-ion batteries.
[0296] Next, the testing methods of the physical parameters and performance parameters mentioned in the embodiments of this application are briefly introduced.
[0297] 1. Test method for powder compaction density
[0298] The compacted density of a material's powder can be tested using methods known in the art. For example, referring to GB / T 24533-2009, an electronic pressure testing machine (such as the UTM7305) can be used. A certain amount of powder is placed on a compaction mold and various pressures are set. The thickness of the powder at each pressure is measured on the machine, and the compacted density at each pressure can be calculated.
[0299] 2. Test method for volume particle size distribution
[0300] The volume particle size distribution of a material can be measured using methods known in the art. For example, referring to GB / T19077-2016 / ISO 13320:2009, a laser diffractometer can be used. After instrument commissioning and background measurement, sample preparation, and light signal acquisition, the instrument is used to calculate the scattering matrix using an appropriate optical model. Finally, the scattered light distribution is converted into a particle size distribution.
[0301] 3. Test method for gram capacity
[0302] PVDF, conductive carbon black (SP), and active materials are mixed in a specific ratio to form a negative electrode slurry. This is then coated onto copper foil and evenly spread with a scraper. The slurry is then dried, cold-pressed, and punched into sheets. The slurry is then assembled with a lithium sheet and separator to form a button cell. A LAND tester is used to perform charge-discharge cycles from 0.005V to 2V to determine the specific gram capacity of the active material.
[0303] 4. Charging time test method
[0304] At 25°C, charge at 0.33C for t minutes to 80% SOC. After standing for 30 minutes, discharge at 1C and then stand for 30 minutes. After 20 cycles, disassemble the battery after full charge and observe whether lithium is deposited at the negative electrode. If there is no lithium deposition, it indicates that the battery's room temperature charging time from 0% to 80% SOC is t minutes.
[0305] 5. Cycle performance test method
[0306] Assemble the full battery and perform a cycle test using a LAND tester with a charge rate of 0.5c and a discharge rate of 1c. The battery is repeatedly charged and discharged, and the number of cycles required for the battery capacity to decay by 80% is calculated, that is, the number of cycles required for the battery's capacity to decay by 80% at room temperature.
[0307] 6. Test method for full charge expansion rate
[0308] At room temperature, measure the thickness d2 of the electrode. After the electrodes are assembled into a battery, charge the battery to 4.2V at 0.5C, let it stand for 3 minutes, disassemble the battery, and measure the thickness d2 of the electrode at this time. The full charge expansion rate can be calculated as (d2-d1) / d1×100%.
[0309] 7. Test method for the proportion of secondary particles
[0310] The ratio (n) of the number of secondary particles in the first carbon-based material to the number of the first carbon-based material can be obtained by detecting the material by scanning electron microscopy. Specifically, the number of particles with secondary particle morphology n2 and the number of all particles n1 in the scanning electron microscope are counted separately. In other words, n = n2 / n1 and then the ratio of the two is calculated. In order to improve the accuracy of the ratio, the above-mentioned number of particles can be counted separately for multiple scanning electron microscopes of the material, and then the proportion of the number of secondary particles can be calculated based on the average of the multiple statistical results.
[0311] As an example, a SEM image can be obtained by:
[0312] A certain mass of the material to be tested (≤2 g) is weighed and adhered to the conductive adhesive. The conductive adhesive is placed on a sample stage and dried. The treated sample stage is sent to a field emission scanning electron microscope (for example, a Zeiss Sigma300 scanning electron microscope) to capture the morphology of the material.
[0313] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A negative electrode plate, characterized in that: The negative electrode plate comprises: A current collector and a film layer disposed on the current collector; The film layer comprises a first portion and a second portion arranged along a thickness direction of the film layer, the first portion being arranged on the current collector, and the second portion being arranged on the first portion; The first part includes a first active material, and the second part includes a second active material. The first active material includes a first carbon-based material, and the second active material includes a second carbon-based material having a coating layer. The powder compaction density of the first active material is greater than the powder compaction density of the second active material.
2. The negative electrode sheet according to claim 1, characterized in that: The powder compaction density ρ2 of the second active material under a pressure of 50000N satisfies: 1.50g / cc≤ρ2≤2.00g / cc; optionally, 1.55g / cc≤ρ2≤1.95g / cc.
3. The negative electrode sheet according to claim 1 or 2, characterized in that: The powder compaction density of the second carbon-based material under a pressure of 50000N is 2-1 Satisfy: 1.60g / cc≤ρ 2-1 ≤1.95g / cc, optionally, 1.65g / cc≤ρ 2-1 ≤1.80g / cc.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The second carbon-based material includes primary particles.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The coating layer includes amorphous carbon.
6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The second carbon-based material satisfies at least one of the following (1)-(3): (1) The specific surface area of the second carbon-based material is SSA2,1.0m 2 / g≤SSA2≤3.0m 2 / g; optionally, 1.3m 2 / g≤SSA2≤2.0m 2 / g; (2) The volume particle size distribution of the second carbon-based material is D V 502, 6.0μm≤D V 502≤18.0μm; optionally, 8.0μm≤D V 502≤15.0μm; (3) The mass specific capacity of the second carbon-based material is C m2 , 345mAh / g≤C m2 ≤360mAh / g; optionally, 348mAh / g≤C m2 ≤358mAh / g.
7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The powder compaction density ρ1 of the first active material under a pressure of 50000N satisfies: 1.70g / cc≤ρ1≤2.05g / cc; optionally, 1.80g / cc≤ρ1≤2.05g / cc.
8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The powder compaction density of the first carbon-based material under a pressure of 50000N is 1-1 Satisfy: 1.80g / cc≤ρ 1-1 ≤2.05g / cc; optionally, 1.90g / cc≤ρ 1-1 ≤2.00g / cc.
9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: The first carbon-based material includes artificial graphite that has been subjected to a micro-oxidation treatment.
10. The negative electrode sheet according to any one of claims 1 to 9, characterized in that: The first carbon-based material includes secondary particles.
11. The negative electrode sheet according to claim 10, characterized in that: In the first carbon-based material, the number ratio n of the secondary particles satisfies: 70%≤n≤90%.
12. The negative electrode sheet according to any one of claims 1 to 11, characterized in that: The first carbon-based material satisfies at least one of the following (4)-(6): (4) The specific surface area of the first carbon-based material is SSA1,1.6m 2 / g≤SSA1≤3.5m 2 / g; optionally, 1.8m 2 / g≤SSA1≤2.8m 2 / g; (5) The volume particle size distribution of the first carbon-based material is D V 501, 10.0μm≤D V 501≤30.0μm; optionally, 13.0μm≤D V 501≤25.0μm; (6) The mass specific capacity of the first carbon-based material is C m1 , 350mAh / g≤C m1 ≤365mAh / g; optionally, 355mAh / g≤C m1 ≤362mAh / g.
13. The negative electrode sheet according to any one of claims 1 to 12, characterized in that: The first active material also includes natural graphite.
14. The negative electrode sheet according to claim 13, characterized in that: The ratio of the mass m2 of the natural graphite to the mass m1 of the first active material satisfies: 0%<m2 / m1≤50%.
15. The negative electrode sheet according to any one of claims 1 to 14, characterized in that: The ratio of the thickness h1 of the first portion to the thickness h of the film layer satisfies: 40%≤h1 / h≤60%.
16. The negative electrode sheet according to any one of claims 1 to 15, characterized in that: The ratio of the thickness h2 of the second portion to the thickness h of the film layer satisfies: 40%≤h2 / h≤60%.
17. A method for preparing a negative electrode sheet, characterized in that: The method comprises: providing a current collector; Preparing a first portion of a film layer on the current collector; wherein the first portion comprises a first active material, and the first active material comprises a first carbon-based material; A second portion of the membrane layer is prepared on the first portion of the membrane layer, wherein the second portion includes a second active material, the second active material includes a second carbon-based material having a coating layer, and the powder compaction density of the first active material is greater than the powder compaction density of the second active material.
18. A battery cell, characterized in that: The battery cell comprises a negative electrode sheet as claimed in any one of claims 1 to 16; or A negative electrode sheet prepared according to the method of claim 17.
19. A battery, characterized in that: The battery comprises the battery cell as claimed in claim 18.
20. An electrical device, characterized in that: The electrical device comprises the battery cell according to claim 18 and / or the battery according to claim 19.
Citation Information
Cited By
Negative electrode sheet, battery, battery pack and electrical device
WO2026194898A1